A 600‐year marine record associated with the dynamics of the eastern Penny Ice Cap (Baffin Island, Nunavut, Canada) - Rodríguez‐Cuicas, María‐Emilia; Montero‐Serrano, Jean‐Carlos; St‐Onge, Guillaume; Normandeau, Alexandre (Journal of Quaternary Science, 2023)
ABSTRACT Two composite sedimentary sequences sampled in the ice‐proximal (12CS) and ice‐distal (02CS) areas of Coronation Fjord (Baffin Island, Nunavut, Canada) were investigated in order to reconstruct the effect of climate variability on 600 years of changes in sediment transfer from the eastern Penny Ice Cap (PIC). Detrital proxies, and physical and sedimentological analyses revealed that glacial meltwater discharges led to frequent rapidly deposited layers (RDLs) in ice‐proximal settings. RDLs in ice‐distal settings involved the sudden release of a large quantity of sediment‐laden water during floods probably originating from adjacent fjords with large sandur deltas. Laminated sediments with ice‐rafted debris throughout the Little Ice Age interval in the ice‐proximal environment suggest that colder conditions promoted glacier growth, leading to successive episodes of turbid hyperpycnal meltwater plumes and iceberg calving in Coronation Fjord. Since 1850 ce , the accelerated Coronation retreat in response to modern warming has led to increased sedimentation rates, abrupt mineralogical and grain size proxy variations and more frequent RDLs. Similar trends between the detrital proxies of the ice‐proximal core and Atlantic Multidecadal Oscillation record and Arctic surface air temperature suggest high connectivity between atmospheric and sea surface temperature variations and PIC dynamics over the last 600 years.
Keywords: Infolettre; Infolettre_Juin_2023

Deciphering the sedimentary imprint of tsunamis and storms in the Lesser Antilles (Saint Martin): A 3500-year record in a coastal lagoon - Fabbri, Stefano C.; Sabatier, Pierre; Paris, Raphaël; Falvard, Simon; Feuillet, Nathalie; Lothoz, Amélie; St-Onge, Guillaume; Gailler, Audrey; Cordrie, Louise; Arnaud, Fabien; Biguenet, Maude; Coulombier, Thibault; et al. (Marine Geology, 2024)
Keywords: Infolettre; Infolettre_Septembre_2024